2009
DOI: 10.1002/jmv.21584
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome surveillance and molecular epidemiology for early detection and tracing of an outbreak of measles in Liguria, Italy

Abstract: The performances of surveillance systems for measles in Europe are poorly investigated, despite the fundamental role they should play in the early detection of outbreaks and in the assessment of the progress towards elimination. A new chief complaint syndrome surveillance system has been developed in Genoa, Italy, using data from the Emergency Department records of the regional reference university hospital and its ability to early detect an outbreak of measles that began during the winter months of 2007/2008 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
(3 reference statements)
0
12
0
Order By: Relevance
“…Otherwise, genotype 2B may have been imported, either from countries where this virus was circulating or from the United Kingdom where the genotype had been endemic since 2006. An interchange between Italy and the United Kingdom has been demonstrated for rubella virus as well as for measles virus [Ansaldi et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, genotype 2B may have been imported, either from countries where this virus was circulating or from the United Kingdom where the genotype had been endemic since 2006. An interchange between Italy and the United Kingdom has been demonstrated for rubella virus as well as for measles virus [Ansaldi et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…No results from subnational analysis were reported, but from analysis by age group. The syndromic surveillance system in Genoa monitored two measles outbreaks with a timeliness of -3.57 weeks on average based on acute care data [ 33 , 34 ]. In this case, subnational surveillance was applied in one study and was connected to a 1.43 week advance detection [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…22,23 The comparison of LRTI incidence obtained from different studies is difficult because of heterogeneity of study design, database and case definitions used. The criteria for confirmation of captured cases used in this study allowed to exclude accesses for acute bronchitis and a revision of a subset of confirmed cases (data not shown) showed that almost all cases fit the case definition of CAP proposed by expert.…”
Section: Discussionmentioning
confidence: 99%
“…The Surveillance System is coordinated by a reference centre (University of Genoa). Syndrome coding, data capture, transmission and processing, statistical analysis to assess indicators of disease activity and alert thresholds, and signal response were operatively described in Ansaldi et al 22,36 The study population consisted of adult subjects (≄ 18-y-old) resident in Genoa, a city of 650,000 inhabitants and capital of Liguria, an administrative region in Northern Italy. The surveyed period covered 3 seasons (2010/2011, 2011/2012, 2012/2013).…”
Section: Methodsmentioning
confidence: 99%